2002
DOI: 10.46989/001c.20314
|View full text |Cite
|
Sign up to set email alerts
|

The Protein Sparing Effects Of High Lipid Levels In Diets For Rainbow Trout (Oncorhynchus Mykiss, W. 1792) With Special Reference To Reduction Of Total Nitrogen Excretion

Abstract: As from January 2010 The Israeli Journal of Aquaculture-Bamidgeh (IJA) will be published exclusively as an on-line Open Access (OA) quarterly accessible by all AquacultureHub (http://www.aquaculturehub.org) members and registered individuals and institutions. Please visit our website (http://siamb.org.il) for free registration form, further information and instructions. This transformation from a subscription printed version to an on-line OA journal, aims at supporting the concept that scientific peer-reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This result could be related to the higher lipase activity in the foregut and the ADC of crude lipid of fish fed the FK8.27 diet, which suggests enhanced lipid digestion of fish. Many studies have also demonstrated the protein-sparing effect of lipid (Yigit et al, 2002;Ai et al, 2004;Aliyu-Paiko et al, 2010;Li et al, 2017;Wang L. et al, 2019). Furthermore, the lipid composition of FK is different from that of the FM, being rich in phospholipids, consisting mainly of 16:0 and 16:1 fatty acids (Calysta data).…”
Section: Discussionmentioning
confidence: 99%
“…This result could be related to the higher lipase activity in the foregut and the ADC of crude lipid of fish fed the FK8.27 diet, which suggests enhanced lipid digestion of fish. Many studies have also demonstrated the protein-sparing effect of lipid (Yigit et al, 2002;Ai et al, 2004;Aliyu-Paiko et al, 2010;Li et al, 2017;Wang L. et al, 2019). Furthermore, the lipid composition of FK is different from that of the FM, being rich in phospholipids, consisting mainly of 16:0 and 16:1 fatty acids (Calysta data).…”
Section: Discussionmentioning
confidence: 99%
“…A suitable protein/energy (P/E) ratio may favor the growth performance of fish due to the proteinsparing effect of lipid. Previously, protein-sparing effect of lipid has been reported in Atlantic cod (Gadus morhua L.) [2], rainbow trout (Oncorhynchus mykiss) [3], cobia (Rachycentron canadum) [4], and brown-marbled grouper (Epinephelus fuscoguttatus (Forskal)) [5]. In recent years, there is a popular trend to increase dietary lipid levels in fish feed to improve protein sparing, growth performance, and farm productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the energy density in diets has been suggested to spare protein for several fish species, especially salmon (Einen & Roem, 1997), rainbow trout (Yigit et al 2002) and catfish (Kim et al, 2012).…”
mentioning
confidence: 99%